Ornithyl amphotericin methyl ester treatment of experimental candidiasis in rats. - Galgiani, J N (1984)
After intravenous Candida albicans infection, rats received orinthyl amphotericin methyl ester, amphotericin B, or diluent intravenously. At doses of 0.1 and 0.5 mg/kg, the drugs were equally effective in preventing deaths. However, at doses of 2.0 mg/kg, mortality after treatment with amphotericin B was greater than that after placebo, whereas orinthyl amphotericin methyl ester was fully protective.